Urban walkability considering pedestrians' perceptions of the built environment: a 10-year review and a case study in a medium-sized city in Latin America. Issue 2 (3rd March 2020) - Arellana, Julian; Saltarín, María; Larrañaga, Ana Margarita; Alvarez, Vilma; Henao, César Augusto
ABSTRACT: Numerous methodologies measuring walkability have been developed over the last years. This paper reviews the Walkability Index (WI) literature of the last decade (2009–2018) and highlights some limitations in the current approaches. Only a few studies have evaluated walkability in Latin America, mainly in big cities but not in medium and small-sized cities in the region, which present their own urbanisation dynamics, security issues, sidewalk invasion problems, and poor planning. Furthermore, most WIs in the literature use objective mesoscale variables to assess walkability in a given area. This paper contributes to filling these gaps by generating new evidence from a medium-sized city in Latin America to question if characteristics of the built environment encourage walking trips, as found in the literature, are transferable among regions. The study also proposes a novel index comprised of microscale and mesoscale built environment variables to assess walkability using virtual tools and considering users' perceptions. The WI estimation relies on ranking probability models. The results of the case study suggest that subjective Security and Traffic Safety are the most crucial factors influencing walkability in these kind of cities, which is different from what is found in the literature from cities in developed countries where Sidewalk Condition and Attractiveness are the most important factors. Security appeared to be strongly associated with a subjective dimension, represented by the fear of crime or perceived risk for crime, instead of the actual occurrence of crimes. This result evidences the importance of the physical attributes of the real world and how they are captured, judged, and processed by pedestrians. Then, regional transferability of WIs needs to be done carefully. Finally, results in this paper highlight the importance of microscale built environment characteristics in the WI formulation in these cities. Results are in line with other research in some cities of the region, which found that microscale variables such as pavement quality and presence of obstacles on the sidewalks are relevant components to promote walkability.